A Study on Country of Origin Towards Purchasing Intention of Cosmetic Products in Malaysia’s Consumer Perspective - Zainuddin, Ahmad Zuhairi; Zainuddin, Nur Zulaikha; Muhamed, Ariff Azly; Ibrahim, Norzawani; Yunus, Noor Azlina Muhamed (Journal of Entrepreneurship, Business and Economics, 2022)
Consumer perceptions of product country-of-origin have shifted from one fresh perspective to another in the current and competitive period of global marketing.  The new view could lead to both positive and negative outcomes in terms of dimensions.  This study aims to contribute and gauge a better understanding of the country of origin toward purchasing intention of cosmetic products in Malaysia’s consumer perspective. The principal objective of this research is to perform a conceptual framework to examine the relationship of country origin towards purchasing intention of cosmetic products among Malaysian consumers. This study proposed to utilise a survey method and the data will be collected specifically in the Klang Valley area.  The originality of this research is on its examining of the relationship among country of origin on purchasing intention of cosmetic product in Malaysian consumers context, something has been ignored in the previous studies. This conceptual model is expected to be contribute to the advancement of knowledge in cosmetic product purchase intention among Malaysian consumers and to get a clear picture of how the factor of the country of origin affects the consumer purchase intention for cosmetic products. Research paper Keywords: Country origin, Cosmetic, Malaysian, Purchasing intention Reference to this paper should be made as follows: Zainuddin, A. Z., Zainuddin, N. Z., Muhamed, A. A., Ibrahim, Z., & Yunus, N. A. M. (2022). A Study On Country Of Origin Towards Purchasing Intention Of Cosmetic Products in Malaysia’s Consumer Perspective. Journal of Entrepreneurship, Business and Economics , 10 (2S2), 138–153.